Mixed convection flow over a horizontal circular cylinder with a constant surface heat flux in a nanofluid - Leony Tham; Roslinda Nazar; Ioan Pop (2015)
The steady laminar mixed convection boundary layer flow from a horizontal circular cylinder in a nanofluid embedded in a porous medium, which is maintained at a constant surface heat flux, has been studied by using the Buongiorno–Darcy nanofluid model for both cases of a heated and cooled cylinder. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme known as the Keller box method. The solutions for the flow and heat transfer characteristics are evaluated numerically and studied for various values of the governing parameters, namely the Lewis number, Brownian number, mixed convection parameter, buoyancy ratio parameter and thermophoresis parameter. It is also found that the boundary layer separation occurs at the opposing fluid flow, that is when the mixed convection parameter is negative. It is also observed that increasing the mixed convection parameter delays the boundary layer separation and the separation can be completely suppressed for sufficiently large values of the mixed convection parameter. The Brownian and buoyancy ratio parameters appear to affect the fluid flow and heat transfer profiles.